Ppy(oxit phức hợp spinel) tổng hợp điện hoá trên graphit ứng dụng làm điện cực catôt trong xử lý môi trường nhờ hiệu ứng Fenton điện hoá - Lê Hiền và cộng sự, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The composite films based on Ppy and mixed spinel oxides (Cu1.5Mn1.5O4 and Ni0.3Co2.7O4) have been electrodeposited on graphite substrate in aqueous solution at a current of 2 mA/cm2. The composites obtained were investigated toward oxygen reduction reaction to hydroperoxyde in Na2SO4 solution with different values of pH. The results showed that the graphite/Ppy(Cu1.5Mn1.5O4)/PPy gives the best electrocatalytic effect at pH3 and their use as cathode for phenol treatment by Electro-Fenton had higher yield than graphite cathode without composite films.